2021
DOI: 10.3390/ijms23010247
|View full text |Cite
|
Sign up to set email alerts
|

Biological Implications of a Stroke Therapy Based in Neuroglobin Hyaluronate Nanoparticles. Neuroprotective Role and Molecular Bases

Abstract: Exogenous neuroprotective protein neuroglobin (Ngb) cannot cross the blood–brain barrier. To overcome this difficulty, we synthesized hyaluronate nanoparticles (NPs), able to deliver Ngb into the brain in an animal model of stroke (MCAO). These NPs effectively reached neurons, and were microscopically identified after 24 h of reperfusion. Compared to MCAO non-treated animals, those treated with Ngb-NPs showed survival rates up to 50% higher, and better neurological scores. Tissue damage improved with the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…Это может служить знаком того, что в 1-й подгруппе ССИГМ наблюдается активация компенсаторных механизмов нейронов. Они, вероятно, заключаются в увеличении активности аэробного гликолиза, что становится возможным благодаря доставке кислорода к митохондриям нейроглобином [17][18][19][20][21].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Это может служить знаком того, что в 1-й подгруппе ССИГМ наблюдается активация компенсаторных механизмов нейронов. Они, вероятно, заключаются в увеличении активности аэробного гликолиза, что становится возможным благодаря доставке кислорода к митохондриям нейроглобином [17][18][19][20][21].…”
Section: Discussionunclassified
“…Повышенное содержание нейроглобина в цитоплазме нейронов в 1-й подгруппе ступенчатой субтотальной ишемии головного мозга с перевязкой обеих общих сонных артерий с интервалом 7 суток также может способствовать оптимизации поступления кислорода в митохондрии. Кроме того, нейроглобин является скэвенджером свободных радикалов, что способствует нормализации прооксидантно-антиоксидантного баланса головного мозга на свободнорадикальном этапе [20][21][22].…”
Section: Discussionunclassified
“…In this regard, we have carried out proteomic studies in an animal model of MCAO, detecting a total of 219 proteins that significantly changed their expression after stroke and treatment with nanoencapsulate-Ngb [55]. Interestingly, our analysis shows a strong upregulation of ATXN2L (Ataxin-2-like protein), a protein involved in the assembly of stress granules (formed in response to diverse cellular stresses) and processing bodies (responsible for cytoplasmic mRNA processing).…”
Section: Unraveling the Neuroprotective Action Mechanisms Of Ngbmentioning
confidence: 92%
“…The pharmaceutical preparation obtained (see later), was highly stable and biocompatible. In addition, it was able to transport the Ngb to the damaged neurons, thus demonstrating its neuroprotective effects against stroke [54][55][56].…”
Section: Current Treatments Against Strokementioning
confidence: 98%
“…Peinado et al [ 13 ] biosynthesized complex protein neuroglobin-hyaluronate nanoparticles (Ngb-NPs) to overcome the difficulty of experienced by Ngb in crossing the blood–brain barrier (BBB) and exerting neuroprotective effects at a brain level in an animal model of stroke (MCAO). They demonstrated that Ngb-NPs, when they are systemically, injected can cross the BBB and increase the survival of MCAO animals.…”
mentioning
confidence: 99%